Alexander Lernet-Holenia und Maria Charlotte Sweceny Briefe 1938-1945 - Dietz, Christopher (2013)
In the centre of this study stand some 154 letters exchanged between the Austrian writer Alexander Lernet-Holenia (1897-1976) and Maria Charlotte ("Lotte") Sweceny (née Stein, 1904-1956), the co-proprietor of the Viennese publishing house Manz, between 1938 and 1945. The transcripts are followed by a commentary that aims to elucidate the historical, individual and geographical references. A methodological note explains the corpus' provenance and method of transcribing and commenting on the letters adopted in the thesis. The last chapter of this study is devoted to Lotte Sweceny, the letters' addressee, and her family background. The letters' existence is due to the fact that the couple was separated by the outbreak of WW II and continued their relationship through correspondence. In September 1939 Lernet took part in the "Wehrmacht's" raid on Poland and was lightly wounded. As a result he spent the rest of the war on a leave of absence in his house in St. Wolfgang and, after September 1941, in Berlin. There, he worked as head of development of the "Heeresfilmstelle" (an office in charge of producing NS propaganda films), writing scripts himself and evaluating those by others. In these years, two of his most important novels, Mars im Widder (Mars in Aries) and Beide Sizilien (The Two Sicilies), were written - both are today considered as running counter to NS propaganda. Lotte Sweceny and her friends found their way into the set of characters and into the plot of Mars in Aries. The collection of poems Die Trophae (The Trophy) also originated from these years. When published in 1946, Lernet dedicated this work - which he considered to be his best - to Lotte Sweceny. The letters contain important background and numerous insights about the genesis and subsequent publication of these works. They also provide biographical details that shed light on the conditions of Lernet-Holenia's life and work during these years. Inter alia, they illuminate the circumstances surrounding Lernet-Holenia's posting to and role in the "Heeresfilmstelle". The writer considered his duties there dull and counterproductive to his actual work and unsurprisingly tried to escape from them as soon as possible. The thesis also addresses certain controversial issues in Lernet-Holenia's biography, in particular his involvement with the Nazi regime and his views on antisemitism: The way Lernet-Holenia writes about the regime and its protagonists in the letters suggests a clear political and intellectual distance to the "Third Reich" and thus reinforces scholarly voices that have, in this regard, already spoken in favor of the author. His use of a certain cipher in his letters even indicates that Lernet-Holenia was in touch with victims (or at least opponents) of the Nazi regime on behalf of Lotte Sweceny, the latter being half-Jewish herself. His personal and private dissociation from the Nazis did not, however, keep Lernet-Holenia from participating in their apparatus as long as he considered it beneficial for his career and/or his personal safety. Lotte Sweceny, who was married to an "Aryan" industrialist, came from the assimilated Jewish bourgeoisie of Vienna. The stimulating atmosphere of her parental home was, in part, the product of the commitment of the two preceding generations to assimilate. The chapter also deals with Lotte's marriage with Otto C. Sweceny - a marriage that was intended as a liberal experiment - and with the circle of friends consisting of architects, writers and others portrayed by the Austrian publicist Milan Dubrovic.